mGCMa is a murine transcription factor that overrides cell fate decisions in Drosophila - Wegner, Michael; et al. (Mechanisms of Development, 1999)
During neural development of Drosophila melanogaster, Glial Cells Missing (GCM), functions as a binary switch that promotes glial cell fate while simultaneously inhibiting the neuronal fate. Sequence similarities between GCM and the recently identified mouse protein mGCMa are strictly limited to the aminoterminal DNA-binding domain. Here we show that mGCMa efficiently activates transcription in Drosophila cells just as Drosophila GCM activates transcription in mammalian cells. Transactivation potential was present in two separate regions of mGCMa outside the DNA-binding domain. One of them mapped to the carboxyterminal 88 amino acids, a location corresponding exactly to the transactivation domain of GCM. Similarities between GCM and mGCMa were also observed in vivo. Overexpression of mGCMa in the developing nervous system of Drosophila embryos led to an increase in glial-like cells at the expense of neurons. Outside the neurogenic region, mGCMa interfered with epidermal development, as evident from changes in celt morphology and marker expression. Thus, mGCMa function is at least partially independent of a cell's predisposition to a neural fate. The potent activity of mGCMa in Drosophila and its extensive functional similarities to GCM make mGCMa a candidate for a regulator of mouse glial development.
UnivIS-Import:2015-03-05:Pub.1999.med.IB.LPCIPDBI.mgcmai
Keywords: Determination; Glia; Glial Cells Missing; Neural development; Transcription